Pengaruh Social Media Marketing, Brand Image, dan Brand Ambassador Terhadap Ekspektasi Konsumen Produk Erigo di Kota Binjai: Penelitian - Robert Vincentius Naibaho; Nana Dyki Dirbawanto; Onan Marakali Siregar (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the influence of Social Media Marketing, Brand Image, and Brand ambassador on Consumer Expectations of Erigo products in Binjai City.The research method used is quantitative with an associative approach. Data were collected through questionnaires distributed to 100 respondents who met specific criteria: consumers who know, follow, and have purchased Erigo products in Binjai. The analysis techniques include validity tests, reliability tests, classical assumption tests, multiple linear regression, partial tests (t-test), simultaneous tests (f-test), and coefficient of determination test, all processed using SPSS software. The results show that Social Media Marketing has a positive and significant effect on consumer expectations with t-count > t-table and significance < 0.05. Brand Image also has a significant positive influence on consumer expectations. Brand ambassador likewise significantly influences consumer expectations. Simultaneously, the three independent variables (Social Media Marketing, Brand Image, and Brand Ambassador) significantly influence consumer expectations of Erigo products. The Adjusted R Square value of 0.782 indicates that 78.2% of consumer expectations can be explained by these three variables, while the remaining 21.8% is influenced by other factors not discussed in this study.